AS CONTRIBUIÇÕES DA ETNOMODELAGEM MATEMÁTICA NO ESTUDO DA GEOMETRIA ESPACIAL - Sonego, Giseli Verginia (2009)
This paper presents the results of a survey of students in the 3rd year of high school, Escola Estadual de Educação Básica João XXIII, the city of São João do Polêsine, RS, in order to analyze the contributions of Mathematical Modeling in Study Space Geometry, while the theme is explored planting rice. We tried to make a connection between the modeling and Ethnomathematics, because the mathematical content to be worked by using our knowledge of economic activities and cultural community where students are placed. The research was a qualitative approach and the development of the activities we used steps of Mathematical Modeling as described in Bassanezi (2002). The instruments chosen for data collection were participant observation, through records and recordings, observation forms and notes made by the teacher and two questionnaires to students participating in the survey with open questions. From the analysis of data was possible to infer that when the math concepts arise from their realities, arouses greater interest and motivation for learning. Regarding the acquisition of knowledge, the primary research evidence was that the pedagogical work, guided by the basic assumptions described in the theoretical framework, promoted effectively pupils' learning. It can be concluded that pedagogical practice showed positive results when used in the classroom.